Workplace Spirituality and Organization Citizenship Behavior (OCB): Employee Engagement Mediation - Bismala, Lila; Hafsah, Hafsah; Handayani, Susi; Indari, Ayu (Jurnal Pendidikan Progresif, 2024)
Abstract: Workplace Spirituality and Organization Citizenship Behavior (OCB): Employee Engagement Mediation. Objective:  The study aimed to analyze the role of employee engagement as a mediating variable in the relationship that occurs between workplace spirituality and organizational citizenship behavior (OCB). Methods: This research is explanatory, using structural equation modeling as a data analysis technique. Data were collected from teachers of state elementary schools in Langkat District, Deli Serdang District, and Medan City, where the total population was 19,096. By using the Slovin method, a sample was determined to be 391 people, from which the researchers selected teachers with the status of civil servant and government employees with employment agreements. Data collection was carried out by distributing questionnaires to research respondents, where the number of questionnaires declared valid was 247. Findings: The results showed that workplace spirituality and employee engagement have a positive effect on OCB; workplace spirituality has a positive effect on employee engagement; and employee engagement acts as a mediating variable in the relationship between workplace spirituality and OCB. Conclusion: Teachers, as an important element in the world of education, are required to always be engaged and show OCB, both towards students, colleagues and the school where they work. With this, teachers will enjoy their work and feel that their work is like educating their own children. Keywords: Workplace spirituality, organizational citizenship behavior, employee engagement.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202420